Anesthesia, Critical Care, & Pain: Analgesia and Anesthesia in Labor and Delivery-I - Kodali Bhavani S, Baheti Dwarkadas K, Parikh Ketan S, Pandya Sunil T; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2013)
The present issue World Clinics Anesthesia, Critical Care, and Pain Management: Analgesia and Anesthesia in Labor and Delivery-I covers all pertinent prerequisites necessary to understand and practice obstetric anesthesia. Having read through the articles, it is evident that every effort has been made to present current methods of obstetric anesthetic practice with great clarity. Since this issue has several contributors, variations in individual practices have been presented so that clinicians can determine what suits the best for their own practice. This journal is useful for every clinician who either practices or would like to practice obstetric anesthesia not only in India but anywhere in the world.
Keywords: Anesthesiology,Obstetrics and Gynecology; Electronic books